Clinical and Genetic Features of Chinese Patients With NIPA1-Related Hereditary Spastic Paraplegia Type 6 - Fu, Jun; Ma, Mingming; Li, Gang; Zhang, Jiewen (Frontiers in Genetics, 2022)
Background: Mutations in the NIPA1 gene cause hereditary spastic paraplegia (HSP) type 6 (SPG6), which is a rare type of HSP with a frequency of less than 1% in Europe. To date, less than 30 SPG6 families and limited NIPA1 mutations have been reported in different ethnic regions. The clinical features are variable. Methods: We screened for NIPA1 mutations by whole exome sequencing or next generation sequencing in 35 unrelated Chinese families with HSP. The clinical manifestations were evaluated. Results: Two variants of NIPA1 were identified in three index patients (3/35, 8.6%), two of whom carried a previously reported common variant c.316G>A (p.G106R), and the third patient harbored a novel likely pathogenic variant c.126C>G (p.N42K). Both variants were de novo in the three index patients. The phenotype was pure HSP in two patients and complicated HSP with epilepsy in the third one. Conclusion: NIPA1-related HSP is more common in China than it in Europe. Both pure and complicated form of HSP can be found. The variant c.316G>A is a hotspot mutation, and the novel variant c.126C>G expands the mutational spectrum. The phenomenon of de novo mutations in NIPA1 emphasizes the need to consider autosomal dominant HSP-related genes in sporadic patients.